The melody lingers on : a novel - Clark, Mary Higgins (Simon & Schuster, 2015)
"Parker Bennett was last seen two years ago on his sailboat in the Caribbean. After he went missing, the world discovered the five-billion-dollar investment fund he managed had also vanished. The scandal over whether Bennett was suicidal or staged his disappearance still continues. Interior designer Lane Harmon finds herself moved by Mrs. Bennett's calm dignity and faith in her husband's innocence. Lane is also drawn to Eric, the Bennett's son. But Lane doesn't realize the closer she gets to the Bennetts, the more she puts her life in jeopardy."